Fruits basket. 6 - Takaya, Natsuki, 1973- (Yen Press, 2016)
"Tohru should be having the time of her life at the Sohmas' vacation home, but ever since Akito arrived, everyone keeps ditching her for him! Yuki had wanted to tell her something important, but now they might not have the time ... Meanwhile, Tohru finally meets the Horse of the zodiac--leaving only the Rooster! Later the fall term begins, and the new student council assembles at last. Tohru goes on her own secret mission to visit Kazuma, desperate to find a way to break the curse. She looks to him for help...but who is the mysterious girl who wants to stop Tohru?" -- Back flap.